A dimeric electron acceptor material with high dielectric constant characteristics, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611225014.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]目前,活性层受体材料主要包括聚合物受体、小分子受体和二聚体受体三大类;聚合物受体虽具备优异的成膜性和良好的机械性能,但其合成过程存在批次间分子量分布不均、结构难以精确控制等固有缺陷,导致器件性能重现性差,严重制约了其商业化应用进程;小分子受体材料结构明确、易于纯化且合成可重复性好,能够有效解决批次稳定性的问题,但该类材料通常具有强结晶性,其电荷传输高度依赖于分子堆积方式,难以在给受体共混体系中获得理想的纳米尺度形貌,从而限制了器件光伏性能的进一步提升
本发明提出一种具有高介电常数特征的二聚电子受体材料及其制备方法和应用,具有高介电常数特征的二聚电子受体材料的化学结构式如式1所示,利用特定的吸电子端基结构及桥连基团的合理布局,使得整个分子表现出显著增强的偶极矩与极化率,从而赋予材料优异的相对介电常数(测试值可达5.09),该结构特征从根本上克服了现有二聚受体材料介电常数偏低的问题。当该材料应用于有机太阳能电池器件时,高介电常数有效改善了活性层内的库仑屏蔽效应,大幅提升了光生激子的解离效率,并显著抑制了电荷复合,使得最终制备的有机太阳能电池器件兼具高短路电流(可达28.45mAcm-2)、高填充因子(可达79.9%)和卓越的光电转换效率(可达20.19%);同时,该材料结构明确、合成可控,可实现优异的批次间重现性和良好的加工成膜性,为高性能有机光伏器件的规模化制备提供了可靠的材料基础。
Smart Images

Figure CN122878339A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of organic electronic materials and device fabrication technology, specifically to a dimer electron acceptor material with high dielectric constant, its preparation method, and its application. Background Technology
[0002] Organic photovoltaic (OPV) devices, with their significant advantages such as flexibility, light weight, semi-transparency, and large-area roll-to-roll printing fabrication, have shown broad application prospects in the field of renewable energy. The active layer, as the core of organic photovoltaic devices, is usually formed by blending electron donor materials and electron acceptor materials to form a bulk heterojunction (BHJ) structure. The donor material is responsible for absorbing photons and generating excitons, while the acceptor material receives and transmits electrons to the external circuit, completing the entire photoelectric conversion process.
[0003] Currently, active layer acceptor materials mainly include three categories: polymer acceptors, small molecule acceptors, and dimer acceptors. Although polymer acceptors have excellent film-forming properties and good mechanical properties, their synthesis process has inherent defects such as uneven molecular weight distribution between batches and difficulty in precise structural control, resulting in poor device performance reproducibility and seriously restricting their commercial application. Small molecule acceptor materials have well-defined structures, are easy to purify, and have good synthesis reproducibility, which can effectively solve the problem of batch stability. However, these materials usually have strong crystallinity, and their charge transport is highly dependent on the molecular stacking mode, making it difficult to obtain ideal nanoscale morphology in acceptor-donor blend systems, thus limiting further improvement of device photovoltaic performance.
[0004] Dimeric acceptor materials combine two small molecule acceptors through specific bridging groups, retaining the advantages of well-defined small molecule structures and batch stability, while also achieving film-forming properties and morphology control comparable to polymers. However, currently, existing dimer acceptor materials generally suffer from low relative dielectric constants, typically below 4. A low dielectric constant weakens the Coulomb shielding effect within the active layer, making it difficult for photogenerated excitons to dissociate efficiently. Furthermore, undissociated excitons are prone to recombination, thus limiting the short-circuit current and fill factor of the device, making it difficult to overcome the bottleneck in overall photoelectric conversion efficiency. A search of existing literature and patents reveals no reports on the directional optimization of the dielectric constant for dimer electron acceptor materials.
[0005] Therefore, developing a dimer electron acceptor material with a high dielectric constant to overcome the aforementioned technical bottlenecks is of great research significance and industrial value for further improving the photoelectric conversion efficiency of organic solar cells. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a dimer electron acceptor material with high dielectric constant, its preparation method and application.
[0007] To achieve the above objectives, the present invention provides the following technical solution: This application provides a dimer electron acceptor material with a high dielectric constant, the general chemical structure of which is shown in Formula 1: ; Formula 1 Where R1 is independently C each time it appears. n H 2n+1 n is an integer between 1 and 100; R2 is independently C for each occurrence. m H 2m+1 m is an integer between 1 and 100; X is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears; Y is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears.
[0008] Preferably, R1 and R2 are each independently selected from C1 to C2. 30 Straight-chain or branched alkyl groups.
[0009] Preferably, X and Y are each independently selected from halogen, nitro, or cyano.
[0010] Preferably, the relative permittivity of the dimer electron acceptor material is greater than or equal to 5.
[0011] A method for preparing a dimer electron acceptor material with high dielectric constant as described above includes the following steps: S1: In the presence of a first catalyst and a first organic solvent, compound 1 is subjected to a first coupling reaction with bis((5-(trimethylstanyl)thiophen-2-yl)methoxy)methane to obtain compound 2; S2: In the presence of a second catalyst and a second organic solvent, compound 2 is subjected to a second condensation reaction with an end-group compound to obtain the dimer electron acceptor material; Wherein, the structural formula of compound 1 is shown in Formula 2, the structural formula of compound 2 is shown in Formula 3, the structural formula of the terminal compound is shown in Formula 4, and the structural formula of compound 3 formed during the reaction is shown in Formula 5: ; Formula 2 Formula 3 ; Formula 4 Formula 5 In equations 2 to 5, R1 is independently C each time it appears. n H 2n+1n is an integer between 1 and 100; R2 is independently C for each occurrence. m H 2m+1 m is an integer between 1 and 100; X is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears; Y is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears.
[0012] Preferably, in step S1, the molar ratio of compound 1 to bis((5-(trimethyltinyl)thiophen-2-yl)methoxy)methane is 1:(0.47-0.49); the reaction temperature of the first coupling reaction is 115℃-120℃, and the reaction time is 10h-14h.
[0013] Preferably, in step S2, the molar ratio of compound 2 to the terminal compound is 1:(6-8); the second condensation reaction is carried out at room temperature for 0.5h-1h.
[0014] An organic solar cell device includes an anode layer, an active layer, and a cathode layer arranged sequentially. The active layer is formed by blending a first donor material and a first acceptor material, wherein the first acceptor material is the aforementioned dimer electron acceptor material with a high dielectric constant.
[0015] Preferably, the first donor material includes PM6, and the mass ratio of PM6 to the dimer electron acceptor material in the active layer is 1:(0.8-1.2).
[0016] Preferably, the raw material system for preparing the active layer further includes a solid additive, wherein the solid additive includes 1,3,5-trichlorobenzene, and the concentration of 1,3,5-trichlorobenzene in the raw material system is 8 mg / mL to 10 mg / mL.
[0017] Compared with the prior art, this application has the following beneficial effects: This invention proposes a dimer electron acceptor material with high dielectric constant, its preparation method, and its applications. The chemical structure of the dimer electron acceptor material with high dielectric constant is shown in Formula 1. Utilizing specific electron-withdrawing end-group structures and a rational arrangement of bridging groups, the entire molecule exhibits significantly enhanced dipole moment and polarizability, thus endowing the material with an excellent relative dielectric constant (tested value up to 5.09). This structural feature fundamentally overcomes the problem of low dielectric constant in existing dimer acceptor materials. When this material is applied to organic solar cell devices, the high dielectric constant effectively improves the Coulomb shielding effect within the active layer, significantly increases the dissociation efficiency of photoexcitons, and significantly suppresses charge recombination, resulting in organic solar cell devices with high short-circuit current (up to 28.45 mA). cm-2 It possesses a high fill factor (up to 79.9%) and excellent photoelectric conversion efficiency (up to 20.19%). At the same time, the material has a well-defined structure, controllable synthesis, and can achieve excellent batch-to-batch reproducibility and good processing and film-forming properties, providing a reliable material basis for the large-scale preparation of high-performance organic photovoltaic devices. Attached Figure Description
[0018] Figure 1 Compound 2 (product 2) in Example 1 of this invention 1 HNMR spectrum; Figure 2 The compound CH8-14 (final product) in Example 1 of this invention 1 HNMR spectrum; Figure 3 The UV-Vis absorption spectra of the solution and the thin film of compound CH8-14 in Example 1 of this invention are shown below. Figure 4 This is a graph showing the relative permittivity of compound CH8-14 in Example 1 of this invention. Figure 5 The images show the current density-photovoltage curve and external quantum efficiency curve of the organic solar cell device in Application Example 1 of this invention; where part A is the current density-photovoltage curve and part B is the external quantum efficiency curve. Detailed Implementation
[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be described in detail below with reference to specific preparation examples, application examples, and performance test results. Those skilled in the art should understand that the described examples are only for illustrating the invention and should not be regarded as limiting the scope of the invention. Unless otherwise specified, the reagents used in this invention are all commercially available analytical grade reagents, and the operations involved are all conventional processes in the field.
[0021] The present invention provides a dimer electron acceptor material with a high dielectric constant. The general formula of the dimer electron acceptor material compound CH8-14A is shown in Formula 1.
[0022] In a preferred embodiment, the material is specifically compound CH8-14, whose chemical structural formula is shown in Formula 6; in Formulas 1 and 6, R1 is independently C each time it appears.n H 2n+1 n is an integer between 1 and 100; R2 is independently C for each occurrence. m H 2m+1 m is an integer between 1 and 100; X is independently selected from H, F, Cl, Br, I, NO2, or CN each time it appears; Y is independently selected from H, F, Cl, Br, I, NO2, or CN each time it appears; as a preferred embodiment, R1 and R2 are each independently selected from C1 to C 30 The straight-chain or branched alkyl group, where X and Y are each independently selected from halogen, nitro or cyano.
[0023] ; Formula 1 ; Formula 6 To endow the material with the target high dielectric constant, the preparation method of this invention adopts a design strategy of first constructing a dimer framework and then introducing strongly polar end groups. The molecular framework is constructed through the first step Stille coupling reaction, and the strongly electron-withdrawing end groups are introduced through the second step condensation reaction, thereby significantly enhancing intramolecular charge transfer (ICT) and improving the polarizability and dielectric constant of the material.
[0024] As an exemplary synthetic preparation process, the first coupling reaction is carried out to prepare the key intermediate; the starting material compound 1 (chemical structure shown in Formula 7) is coupled with bis((5-(trimethylstanyl)thiophen-2-yl)methoxy)methane in the presence of a palladium catalyst via Stille coupling to generate compound 2 (chemical structure shown in Formula 8). The specific chemical reaction route of this step is shown in the S1 reaction route diagram.
[0025] ; S1 reaction route diagram ; Formula 7 Formula 8 Specifically, the process parameters for step S1 are as follows: 0.3 g of compound 1 and 56 mg of bis((5-(trimethyltinyl)thiophen-2-yl)methoxy)methane are added to a two-necked reaction flask. 20 mL of anhydrous toluene is used as the reaction solvent, and 23 mg of tetrakis(triphenylphosphine)palladium (Pd(PPh3)4) is added as a catalyst under an argon atmosphere. The resulting mixture is reacted in an oil bath at 120°C for 12 hours. After the reaction, the product is extracted with dichloromethane, dried over anhydrous sodium sulfate, and then eluted by column chromatography with an organic eluent (petroleum ether and dichloromethane in a 1:1 volume ratio) to obtain pure product 2, with a yield of 0.17 g and a recovery rate of 60%. This intermediate compound 2...1 HNMR spectrum as follows Figure 1 As shown.
[0026] The second condensation reaction is then carried out by adding 0.17 g of the above compound 2 and 0.12 g of the end-group compound (CAS No.: 2197167-50-1) to a single-necked reaction flask; wherein, the chemical structural formula of the end-group compound is shown in Formula 9, and the chemical structural formula of the reaction intermediate compound 3 involved in the condensation reaction is shown in Formula 10; in step S2, the end groups are condensed to both ends of the dimer framework under the action of a catalyst, thus completing the introduction of polar end groups. The specific chemical reaction route of this step is shown in the reaction route diagram of S2.
[0027] ; S2 reaction route diagram ; Formula 9 Formula 10 Specifically, the process parameters for step S2 are as follows: 20 mL of anhydrous toluene is added to the reaction flask as a solvent, followed by 0.1 mL of acetic anhydride (Ac₂O) and 0.1 mL of boron trifluoride diethyl ether (BF₃·OEt₂) solution as catalysts. The mixture is stirred at room temperature for 0.5 hours. After the reaction is complete, the reaction solution is directly loaded onto a column chromatography column. The eluent is still a 1:1 volume ratio mixture of petroleum ether and dichloromethane. The target product is collected and concentrated under reduced pressure to obtain 0.16 g of a dark solid product, namely the target compound CH₈-14 (corresponding to formula 6), with a yield of 73%. The final product CH₈-14... 1 HNMR spectrum as follows Figure 2 As shown.
[0028] In the fabrication of organic solar cell devices, this invention provides a typical device fabrication process. First, an ITO conductive glass substrate is sequentially ultrasonically cleaned for 20 minutes each with detergent, deionized water, and isopropanol solvent in an ultrasonic cleaner. The cleaned ITO conductive glass substrate is then treated in an ultraviolet-ozone chamber for 15 minutes to obtain a treated ITO conductive glass substrate. Next, an anode modification layer is prepared by mixing hole transport material Ph-4PACz with a 0.4 mg / mL methanol solution at a volume ratio of 1:1. This solution is then spin-coated onto the upper surface of the treated ITO conductive glass substrate at 3000 rpm for 20 seconds using a spin coater. The substrate is then heat-annealed at 100°C for 10 minutes to form a 15 nm thick anode modification layer. Finally, an active layer is prepared by mixing donor material PM6 and acceptor material CH8-14 in a predetermined ratio and dissolving them in... A solution with a total concentration of 6 mg / mL was prepared in chloroform and stirred on a hot plate at 60°C for 1 hour. Using a spin coater, this mixed solution was applied to the surface of the anode modification layer away from the ITO conductive glass substrate at 2000 rpm for 20 seconds, followed by thermal annealing at 100°C for 5 minutes to form an active layer with a thickness of 100 nm. Subsequently, the cathode interface layer was prepared by dissolving PNDIT-F3N in a mixed solvent of methanol and glacial acetic acid (1 mg / mL, prepared at a volume percentage of 99.7%:0.3%) and stirring for 3 hours. Using a spin coater, this solution was applied to the surface of the active layer away from the anode modification layer at 3300 rpm for 20 seconds to form a cathode interface layer with a thickness of 5 nm. Finally, a 150 nm thick Ag metal electrode was deposited on the surface of the cathode interface layer away from the active layer using a vacuum evaporation process to form the final organic solar cell device.
[0029] To fully verify the superior performance of the material of the present invention under different formulations, different comparative groups were further set up with reference to the above device preparation process. Among them, Application Examples 1 to 3 mainly investigated the effect of different mass ratios of PM6 and CH8-14 on device performance, and the specific ratios are detailed in Table 1. Application Examples 4 to 9 mainly investigated the promoting effect of adding different types and concentrations of solid additives on the photovoltaic performance of the device. Among them, Application Examples 4 to 6 added different concentrations of 2-CN (2-chloronaphthalene), and Application Examples 7 to 9 added different concentrations of 1,3,5-trichlorobenzene (TCB), and the detailed parameters are shown in Table 2.
[0030] Table 1. Mass ratio of active layer materials in Application Examples 1 to 3
[0031] Table 2. Types and concentrations of additives in Application Examples 4 to 9
[0032] Further systematic performance characterization of the materials and devices was conducted. Firstly, the absorption spectrum of compound CH8-14 was measured. CH8-14 was dissolved in chloroform to obtain a solution, which was then spun onto a quartz plate at 1200 rpm to obtain a CH8-14 thin film. The UV-Vis absorption spectra of both the CH8-14 solution and the CH8-14 thin film were measured. The test results are as follows: Figure 3 As shown, the CH8-14 solution exhibits excellent absorption in the wavelength range of 300 nm to 1000 nm, with a maximum absorption peak at 793 nm. The CH8-14 film, however, shows a significant red shift relative to the solution and possesses a wider absorption range, with a maximum absorption peak at 842 nm. This indicates that the compound CH8-14 prepared in this embodiment possesses excellent near-infrared absorption characteristics. Subsequently, the dielectric constant of the compound CH8-14 was tested. CH8-14 was dissolved in chloroform, and a CH8-14 film was obtained by spin-coating on a quartz plate at 1200 rpm. The dielectric constant of this film was then tested, and the results are as follows: Figure 4 As shown, the relative permittivity of CH8-14 is as high as 5.09, which is attributed to the unique molecular structure design of this invention, namely, the synergistic effect of the dimer framework and electron-withdrawing end groups greatly enhances the molecular polarizability, indicating that the compound of this invention has a significant high permittivity.
[0033] Under standard sunlight (AM1.5G) irradiation conditions, the open-circuit voltage of the organic solar cell devices in Examples 1 to 9 was tested using a computer-controlled Keithley 2400 digital source meter. V oc ), short-circuit current density ( J sc ), integral short-circuit current density ( J sc cal The fill factor (FF) and photoelectric conversion efficiency (PCE) were tested, and the test results are shown in Table 3.
[0034] Table 3 Photovoltaic performance parameters of organic solar cell devices in Application Examples 1 to 9
[0035] As can be seen from the test results in Table 3, the devices fabricated using compound CH8-14 prepared in this invention as the acceptor material all exhibit significantly high short-circuit current and high fill factor; among them, Application Example 8 (with 10 mg / mL of 1,3,5-trichlorobenzene added to the active layer) shows the best overall performance, with its open-circuit voltage ( V ocThe voltage is 0.888V, and the short-circuit current density is ( J sc Up to 28.45 mA cm -2 Integral short-circuit current density ( J sc cal The value is 27.30 mA. cm -2 The fill factor (FF) is as high as 79.9%, and the photoelectric conversion efficiency (PCE) reaches 20.19%. Figure 5 (Where A is the current density-photovoltage curve of the device in Application Example 1, and B is the external quantum efficiency curve of the device in Application Example 1) shows that this series of devices has excellent rectangular JV curve characteristics, and the external quantum efficiency (EQE) remains above 80% in a wide spectral range from 350 nm to 900 nm. These results fully demonstrate that the material of the present invention effectively promotes exciton dissociation and charge collection through high dielectric constant, and the material can be used efficiently to prepare high-performance organic solar cell devices.
[0036] In summary, organic solar cell devices prepared using the compound CH8-14 provided by this invention as a novel acceptor material exhibit excellent high dielectric constant characteristics, with a photoelectric conversion efficiency reaching up to 20.19%. Furthermore, this compound possesses advantages such as precise molecular weight, controllable structure, and ease of purification, making it highly suitable for preparing stable, flexible, and mass-producible organic solar cell devices.
[0037] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0038] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A dimer electron acceptor material with a high dielectric constant, characterized in that, The general chemical structural formula of the dimer electron acceptor material is shown in Formula 1: ; Formula 1 Where R1 is independently C each time it appears. n H 2n+1 n is an integer between 1 and 100; R2 is independently C for each occurrence. m H 2m+1 m is an integer between 1 and 100; X is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears; Y is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears.
2. The dimer electron acceptor material with high dielectric constant according to claim 1, characterized in that, R1 and R2 are each independently selected from C1 to C2. 30 Straight-chain or branched alkyl groups.
3. The dimer electron acceptor material with high dielectric constant according to claim 1, characterized in that, X and Y are each independently selected from halogen, nitro, or cyano groups.
4. The dimer electron acceptor material with high dielectric constant according to any one of claims 1 to 3, characterized in that, The relative permittivity of the dimer electron acceptor material is greater than or equal to 5.
5. A method for preparing a dimer electron acceptor material with high dielectric constant as described in any one of claims 1 to 4, characterized in that, Includes the following steps: S1: In the presence of a first catalyst and a first organic solvent, compound 1 is subjected to a first coupling reaction with bis((5-(trimethylstanyl)thiophen-2-yl)methoxy)methane to obtain compound 2; S2: In the presence of a second catalyst and a second organic solvent, compound 2 is subjected to a second condensation reaction with an end-group compound to obtain the dimer electron acceptor material; Wherein, the structural formula of compound 1 is shown in Formula 2, the structural formula of compound 2 is shown in Formula 3, the structural formula of the terminal compound is shown in Formula 4, and the structural formula of compound 3 formed during the reaction is shown in Formula 5: ; Formula 2 Formula 3 ; Formula 4 Formula 5 In equations 2 to 5, R1 is independently C each time it appears. n H 2n+1 n is an integer between 1 and 100; R2 is independently C for each occurrence. m H 2m+1 m is an integer between 1 and 100; X is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears; Y is independently selected from H, F, Cl, Br, I, NO2 or CN each time it appears.
6. The preparation method according to claim 5, characterized in that, In step S1, the molar ratio of compound 1 to bis((5-(trimethyltinyl)thiophen-2-yl)methoxy)methane is 1:(0.47-0.49); the reaction temperature of the first coupling reaction is 115℃-120℃, and the reaction time is 10h-14h.
7. The preparation method according to claim 5, characterized in that, In step S2, the molar ratio of compound 2 to the terminal compound is 1:(6-8); the second condensation reaction is carried out at room temperature for 0.5h-1h.
8. An organic solar cell device, characterized in that, It includes an anode layer, an active layer and a cathode layer arranged sequentially, wherein the active layer is formed by blending a first donor material and a first acceptor material, and the first acceptor material is a dimer electron acceptor material with high dielectric constant as described in any one of claims 1 to 4.
9. The organic solar cell device according to claim 8, characterized in that, The first donor material includes PM6, and the mass ratio of PM6 to the dimer electron acceptor material in the active layer is 1:(0.8-1.2).
10. The organic solar cell device according to claim 8 or 9, characterized in that, The raw material system for preparing the active layer also includes solid additives, including 1,3,5-trichlorobenzene, wherein the concentration of 1,3,5-trichlorobenzene in the raw material system is 8 mg / mL to 10 mg / mL.